An evaluation of a Shockroom located CT scanner: a randomized study of early assessment by CT scanning in trauma patients in the bi-located trauma center North-West Netherlands (REACT trial) - Saltzherr, Teun P (BioMed Central, 2008)
BACKGROUND: Trauma is a major source of morbidity and mortality, especially in people below the age of 50 years. For the evaluation of trauma patients CT scanning has gained wide acceptance in and provides detailed information on location and severity of injuries. However, CT scanning is frequently time consuming due to logistical (location of CT scanner elsewhere in the hospital) and technical issues. An innovative and unique infrastructural change has been made in the AMC in which the CT scanner is transported to the patient instead of the patient to the CT scanner. As a consequence, early shockroom CT scanning provides an all-inclusive multifocal diagnostic modality that can detect (potentially life-threatening) injuries in an earlier stage, so that therapy can be directed based on these findings. METHODS/DESIGN: The REACT-trial is a prospective, randomized trial, comparing two Dutch level-1 trauma centers, respectively the VUmc and AMC, with the only difference being the location of the CT scanner (respectively in the Radiology Department and in the shockroom). All trauma patients that are transported to the AMC or VUmc shockroom according to the current prehospital triage system are included. Patients younger than 16 years of age and patients who die during transport are excluded. Randomization will be performed prehospitally. Study parameters are the number of days outside the hospital during the first year following the trauma (primary outcome), general health at 6 and 12 months post trauma, mortality and morbidity, and various time intervals during initial evaluation. In addition a cost-effectiveness analysis of this shockroom concept will be performed. Regarding primary outcome it is estimated that the common standard deviation of days spent outside of the hospital during the first year following trauma is a total of 12 days. To detect an overall difference of 2 days within the first year between the two strategies, 562 patients per group are needed. (alpha 0.95 and beta 0.80). DISCUSSION: The REACT-trial will provide evidence on the effects of a strategy involving early shockroom CT scanning compared with a standard diagnostic imaging strategy in trauma patients on both patient outcome and operations research. TRIAL REGISTRATION: ISRCTN55332315